2019
DOI: 10.3389/fmats.2019.00193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Structure and Properties of Poly(Vinylidene Fluoride)/Montmorillonite-Polypyrrole Nanocomposites Prepared by Electrospinning and Solution Casting

Abstract: In this work, non-woven mats of poly(vinylidene fluoride; PVDF) containing different weight fractions (2.5, 5, 10, and 12.5 wt%) of a nanostructured conductive additive based on montmorillonite-dodecylbenzenesulfonic acid-doped polypyrrole (Mt-PPy.DBSA) have been prepared by electrospinning. The effect of Mt-PPy.DBSA content on the properties of PVDF solution, mats morphology, thermo-mechanical, and electrical properties was investigated. Polymorphism of PVDF/Mt-PPy.DBSA mats was investigated by Fourier Transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…There have also been published results of investigations of the EMI shielding effectiveness of conductive PPy/montmorillonite composites, 112 PPy/thermoplastic polyurethane/montmorillonite composites 113 or PPy/poly(vinylidene flouride)/montmorillonite composites. 114 The results demonstrated that such composites are promising materials for EMI shielding applications.…”
Section: Materials Used For Emi Shieldingmentioning
confidence: 85%
“…There have also been published results of investigations of the EMI shielding effectiveness of conductive PPy/montmorillonite composites, 112 PPy/thermoplastic polyurethane/montmorillonite composites 113 or PPy/poly(vinylidene flouride)/montmorillonite composites. 114 The results demonstrated that such composites are promising materials for EMI shielding applications.…”
Section: Materials Used For Emi Shieldingmentioning
confidence: 85%
“…The additives formed by combination between nanoclays and polymeric structures has been considered as privileged way for the manufacturing PVDF blended membrane, but several questions are posed for the techniques of synthesis. In this context, research work has been realized by Schiefferdecker et al [14] based on the comparison between electectrospining and casting methods when nanocomposite membranes PVDF/Mt-PPy. DBSA was prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Figure3A,B displays SEM images of aligned TPU and TPU/PANI mats, respectively. It was observed that a massive buildup of PANI was present on the fiber surfaces, to the extent that it created a rough and irregular wall-like structure, making the fibers not visible, this indicates successful incorporation of PANI into the TPU matrix 32. …”
mentioning
confidence: 99%